Integrative revision of the Blommersia wittei complex, with description of a new species of frog from western and north-western Madagascar - Vences, Miguel; Multzsch, Malte; Köhler, Jörn; Crottini, Angelica; Andreone, Franco; Rakotoarison, Andolalao; Scherz, Mark D.; Glaw, Frank (Zootaxa, 2023)
Frogs of the Blommersia wittei complex are widespread in western and northern Madagascar, and are one of two clades of the family Mantellidae that have colonized the Comoran island of Mayotte. Based on a comprehensive set of DNA sequences of the mitochondrial 16S rRNA gene and the nuclear-encoded RAG1 and SACS genes, integrated with morphological and bioacoustic data, we here analyze the genetic differentiation of populations of this complex across Madagascar. We confirm that a candidate species named B. sp. Ca5 in previous studies represents a genetically well-defined evolutionary lineage distributed over much of western Madagascar, which we describe herein as Blommeria bara sp. nov. based on its molecular and bioacoustic differentiation. Blommersia wittei occurs across northern Madagascar but its type locality Ambanja, at the lower Sambirano river, is very close to the range of another, newly discovered microendemic lineage that was only found at two sites along the upper Sambirano river (here named as candidate species B. sp. Ca12). The B. wittei complex thus provides an example of a clade of closely related Malagasy frogs that contains species widespread over hundreds of kilometers, as well as extreme microendemics. For a full resolution of this species complex, more data need to be collected on the geographical contact among these two lineages, on the morphology and bioacoustics of B. sp. Ca12, and on the north-eastern populations of B. wittei at Sambava, which are weakly differentiated in mitochondrial genes but differ in bioacoustics and possibly in the extent of foot webbing.